Academic Resilience through Reality Approach Group Counseling: Quantitative Study taking Social Support and Independence into Account - Rahmi Sopah; Yosef Yosef; Ratna Sari Dewi; Kushendar Kushendar; Purwati Purwati (Bulletin of Counseling and Psychotherapy, 2023)
Academic resilience is the ability of students to overcome challenges in the academic world. This study aims to develop a counseling approach that is valid and effective in helping students develop this resilience, considering the role of social support and their level of independence. This study examines the effectiveness of reality counseling in increasing students' academic resilience. Using a quantitative design, the experimental group received the reality approach group counseling, while the control group did not receive the intervention. Data on the level of academic resilience was collected before and after the group counseling intervention. The analysis results show that the experimental group experienced a significant increase in academic resilience, with a significance value of F =124.582 (sig) .000 < .005. The difference in effect can be seen in each group for the experimental group has a value of sig .122 > .005, so the significant effect on group 1 and group 3 is different from group 3 (control group) the value is sig .000 <.005. the difference in the treatment of each sig value > .005 between the variables of independence and social support does not significantly affect academic resilience. These findings indicate that reality counseling is effective in helping students cope with academic challenges more adaptively. Nonetheless, note the study's limitations, such as the limited sample size and other unmeasured factors. The conclusion of this study emphasizes that reality counseling can be used as a relevant intervention to increase students' academic resilience.